2021
DOI: 10.4239/wjd.v12.i6.786
|View full text |Cite
|
Sign up to set email alerts
|

Oral glucose tolerance test in diabetes, the old method revisited

Abstract: The oral glucose tolerance test (OGTT) has been widely used both in clinics and in basic research for a long time. It is applied to diagnose impaired glucose tolerance and/or type 2 diabetes mellitus in individuals. Additionally, it has been employed in research to investigate glucose utilization and insulin sensitivity in animals. The main aim of each was quite different, and the details are also somewhat varied. However, the time or duration of the OGTT was the same, using the 2-h post-glucose load glycemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…OGTT is commonly used in clinics and in research [ 33 ] for the diagnosis of type 2 diabetes mellitus and impaired glucose tolerance [ 34 ]. It has also been used for the investigation of glucose sensitivity and glucose utilization in animals in research.…”
Section: Discussionmentioning
confidence: 99%
“…OGTT is commonly used in clinics and in research [ 33 ] for the diagnosis of type 2 diabetes mellitus and impaired glucose tolerance [ 34 ]. It has also been used for the investigation of glucose sensitivity and glucose utilization in animals in research.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this might be that probiotic supplementation may reduce blood glucose not by directly improving β-cell function. 44 The plasma glucose levels obtained during the OGTT were related to both insulin sensitivity and secretion, reflecting the function of β-cells. 45,46 Though the underlying mechanisms have not been fully elucidated, there were studies showing that probiotics could increase insulin sensitivity and reduce autoimmune responses by modulating intestinal microbiota, thus decreasing the inflammatory reactions and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from OGTT revealed that, the blood glucose level was highest at 30 minutes, post glucose administration and declined gradually up till 120 minutes of acute phase of the OGTT. The ability of the Wistar rats to metabolize the administered glucose, leading to decline in its concentration after 30 minutes of administration suggest the extract does not cause glucose tolerance nor affects the sensitivity of glucose to liver and other peripheral tissues (Ernsberger and Koletsky, 2012; Kuo et al, 2021), hence this suggests that ELEHA may possess antihyperglycaemic activity.…”
Section: Discussionmentioning
confidence: 99%